Calcimycin mediates apoptosis in breast and cervical cancer cell lines by inducing intracellular calcium levels in a P2RX4-dependent manner - Neha; Ranjan, Prashant; Das, Parimal (Biochimica et biophysica acta. General subjects, 2024)
Calcimycin (A23187) is a polyether antibiotic and divalent cation ionophore, extracted from Streptomyces chartrecensis. With wide variety of antimicrobial activities, it also exhibits cytotoxicity of tumor cells. Calcimycin exhibit therapeutic potential against tumor cell growth; however, the molecular mechanism remains to be fully elucidated. Present study explores the mechanism of calcimycin-induced apoptosis cancer cell lines. Apoptotic induction in a dose-dependent manner were recorded with MTT assays, Phase contrast imaging, wound healing assay, fluorescence imaging by DAPI and AO/EB staining and FACS using cell line model. Mitochondrial potential was analyzed by TMRM assay as Ca signaling is well known to be influenced and synchronized by mitochondria also. Calcimycin induces apoptosis in dose dependent manner, also accompanied by increased intracellular calcium-level and expression of purinergic receptor-P2RX4, a ligand-gated ion channel. Calcimycin tends to increase the intracellular calcium level, mRNA expression of ATP receptor P2RX4, and phosphorylation of p38. Blocking of either intracellular calcium by BAPTA-AM, P2RX4 expression by antagonist 5-BDBD, and phospho-p38 by SB203580, abrogated the apoptotic activity of calcimycin. Taken together, these results show that calcimycin induces apoptosis in P2RX4 and ATP mediated intracellular Ca and p38 MAPK mediated pathway in both the cancer cell lines. This study explored a new mode of action for calcimycin in cancer that could be potentially employed in future studies for cancer therapeutic research. This study disentangles that the calcimycin-induced apoptotic cell death is P2RX4 and ATP involved, intracellular Ca and p38 MAPK mediated pathway.